Vascular cognitive impairment after ischemic stroke - Made Wulan Utami Dewi; A. A. A Putri Laksmidewi (International Journal of Biomedical Science and Travel Medicine, 2024)
Background Post-stroke cognitive impairment is the leading cause of post-stroke morbidity and mortality worldwide. This impairment is often associated with ischemic stroke and intracerebral hemorrhage. Cognitive impairment could affect attention, memory, language, orientation, and executive and social functioning domains. Case We reported a male patient, 45 years old, Javanese, who came with confusion and memory impairment. When asked a question, the patient tends to think and answer slowly with a wrong response. He also felt weakness in the right half of the body, slurred speech, pursed lips, and had been diagnosed with ischemic stroke. One week after he was sent home, patient still had difficulty arranging words to form a sentence and could not work. Cognitive function screening showed impairment in attention and memory domain with a MOCA-INA score of 19/30. Patients received antihypertensive therapy, dual antiplatelet, statin, and cognitive stimulation. His condition improved with this treatment. Conclusion Early identification of cognitive impairment could reduce morbidity in stroke patients.